Management of Muscle Spasms in Adult Patients with Cerebral Palsy. Issue 12 (December 2021) - Korntner, Samuel; Elko, Catherine; Edwards, Linda; Jacob, Rafik
Abstract : The purpose of this literature review was to further explore available treatment options for muscle spasms in adults with cerebral palsy (CP). The treatment of CP has largely been explored in the pediatric population. Spasticity treatment in children includes but is not limited to physical therapy, pharmacological therapy, botulinum toxin, and surgical treatment. In this article, it was the authors' goal to review existing treatments for muscle spasticity in CP to provide an overview of possible treatments for adults. Abstract: As medical care advances, there is a growing number of adult patients with cerebral palsy. The spastic form is characterized by muscle hypertonicity, hyperreflexia, and spasticity, which are associated with worse quality of life, poor functionality, and pain. This literature review attempts to explore the existing treatments for spasticity in cerebral palsy to provide insight into potential treatments in the adult population. The types of treatments are broadly categorized into physical therapy, pharmacologic treatments, botulinum toxin, surgical treatments, and alternative options.